Do local elections predict the outcome of the next general election? Forecasting British general elections from local election national vote share estimates. (March 2016) - Prosser, Christopher
Abstract: This article outlines a method for forecasting British general elections from national level vote shares at local elections. Although local elections are notionally 'local', the evidence suggests that they at least partly mirror national electoral fortunes. A simple general election vote share on local election vote share regression model that accounts for partisan differences and incumbency effects fits past data with reasonable accuracy. Based on the results of the 2013 and 2014 local elections, the model forecast a 56% probability of hung parliament, with a 78% probability of the Conservatives receiving the largest share of the vote. Highlights: Local election results are used to give a long-range forecast of the 2015 UK general election. The forecast is based on the 2013 and 2014 local election results. The forecast vote shares are Con 35.25, Lab, 31.05, Lib Dem 15.675, and UKIP 12.5. The forecast seats are Con 296, Lab 287, and Lib Dem 38.